Alcohol use and problem drinking in South Africa: Results from a national-population-based survey 2014-2015. Issue 2 (4th March 2018) - Peltzer, Karl; Pengpid, Supa
Abstract : The aim of this study was to estimate the pattern of alcohol use among South African adults by their socio-demographic and health status indicators. We analysed data from a 2014–2015 South African national population-based survey which sampled 22 752 adults (mean age 37.1 years, SD = 17.6, age range of 15–109 years). Results indicate 3.9% were hazardous or harmful alcohol users. In adjusted logistic regression analysis, both men and women who self-reported to use tobacco, and women to have hypertension, were at higher risk for harmful alcohol use. Age and socioeconomic status moderated harmful alcohol use among men so that those in middle age (35–49 years) and with above average household income were at lower risk for hazardous or harmful alcohol use. Socio-demographic factors appear to primarily influence risk for hazardous or harmful alcohol use among South African adults.